Functional and Nonfunctional Forms of CquiOR91, an Odorant Selectivity Subunit of Culex quinquefasciatus - Hughes, David T. (Chem Senses, 2017)
In Culex quinquefasciatus, CquiOR91 is the ortholog of 2 larvae-specific odorant receptors (ORs) from Anopheles gambiae (Agam\Or40, previously shown to respond to several odorant ligands including the broad-spectrum repellent N,N-diethyl-3-methylbenzamide, DEET) and Aedes aegypti (Aaeg\Or40). When we cloned full-length CquiOR91 from a Culex quinquefasciatus larval head RNA sample, we found 2 alleles of this OR, differing at 9 residues. Functional analysis using the Xenopus oocyte expression system and 2-electrode voltage clamp electrophysiology revealed one allele (CquiOR91.1) to be nonfunctional, whereas the other allele (CquiOR91.2) was functional. Receptors formed by CquiOR91.2 and Cqui\Orco responded to (−)-fenchone, (+)-fenchone, and DEET, similar to what has been reported for Agam\Or40. We also identified 5 novel odorant ligands for the CquiOR91.2 + Cqui\Orco receptor: 2-isobutylthiazole, veratrole, eucalyptol, d-camphor, and safranal, with safranal being the most potent. To explore possible reasons for the lack of function for CquiOR91.1, we generated a series of mutant CquiOR91.2 subunits, in which the residue at each of the 9 polymorphic residue positions was changed from what occurs in CquiOR91.2 to what occurs in CquiOR91.1. Eight of the 9 mutant versions of CquiOR91.2 formed functional receptors, responding to (−)-fenchone. Only the CquiOR91.2 Y183C mutant was nonfunctional. The reverse mutation (C183Y) conferred function on CquiOR91.1 , which became responsive to (−)-fenchone and safranal. These results indicate that the “defect” in CquiOR91.1 that prevents function is the cysteine at position 183.